Readiness of Al-Islam and Kemuhammadiyahan (ISMU) Teachers in Implementing 2013 in Junior High Schools (Adabiyah: Jurnal Pendidikan Islam, 2017)
SMP Muhammadiyah subjects Al-islam and Kemuhammadiyah (ISMU) plays a very important role to form insan a character, character and Muslim personality. Because that is the benchmark of the success of this ISMU subject is the main lies in changes in student behavior, attitude (attitude) and mental. ISMU Education which is a mandatory lesson taught in SMP Muhammadiyah must be able to realize what aspired muhammadiyah organization. But please note what is currently done related to teaching ISMU needs to be evaluated from learning to Out put from learning outcomes. The purpose of this study to determine the readiness of ISMU teachers in the implementation of Curriculum 2013 in SMP Muhammadiyah 2 Taman-Sidoarjo in terms of planning, implementation, assessment of learning outcomes. This study uses a quantitative approach. Data collection techniques used are questionnaires, documentation, observation. Meanwhile, the technique of examining the validity of the data used extension of participation, discussion of colleagues, Triangulation. Result of data in terms of learning process planning 76,93%, implementation of learning process 75,25%, and assessment of learning process 76,47% indicate Category Ready with range span (61% -80%).